Multi-grain-boundary Cu-based catalyst for electrocatalytic reduction of low-concentration CO and preparation method of multi-grain-boundary Cu-based catalyst

By electrodeposition of polygranular boundary Cu-based catalyst on the gas diffusion layer, the problem of low Faraday efficiency when electrocatalyzed reduction of low CO concentration is solved, efficient CO reduction is achieved, and the catalyst has good stability and low cost preparation.

CN119287419APending Publication Date: 2025-01-10BEIJING UNIV OF TECH

Patent Information

Application Number
CN202411639309.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art has low Faraday efficiency when electrocatalytic reduction of low CO concentrations, and nanotwin Cu catalysts have not been used in the application of electrocatalytic reduction of CO.

Method used

The polygranular boundary Cu-based catalyst is loaded on the gas diffusion layer by electrodeposition method, and gelatin is added to concentrated sulfuric acid, anhydrous copper sulfate and sodium chloride solutions, and polygranular Cu-based Cu-based catalyst is formed on the gas diffusion layer by direct current electroplating. Catalysts with rich twin structure and grain boundaries.

Benefits of technology

It improves the electron transfer efficiency during electrocatalysis, reduces the potential required for CO reduction, and improves the Faraday efficiency of C2+ products. The preparation process is simple and low cost, and the catalyst has good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005138009240000011
    Figure HDA0005138009240000011
  • Figure HDA0005138009240000012
    Figure HDA0005138009240000012
  • Figure HDA0005138009240000021
    Figure HDA0005138009240000021
Patent Text Reader

Abstract

The invention discloses a multi-grain-boundary Cu-based catalyst for electrocatalytic reduction of low-concentration CO and a preparation method, and belongs to the field of catalyst preparation, and the preparation method comprises the following steps: (1) dissolving a certain amount of concentrated sulfuric acid, anhydrous cupric sulfate, sodium chloride, gelatin and the like in water at a certain temperature in sequence to prepare an electroplating solution; and (2) placing the electroplating solution in an electrolytic bath, and electrically depositing a certain amount of Cu on the gas diffusion layer under the conditions of certain temperature, voltage and current density by taking the foamy copper as an anode and the gas diffusion layer as a cathode to prepare the catalyst. The gas diffusion layer loaded multi-grain-boundary Cu-based catalyst provided by the invention can be used for efficiently electrocatalytically reducing low-concentration CO (5% CO / N2) under the conditions of normal temperature and normal pressure, reduction products are mainly ethanol, acetic acid and the like, and the total Faraday efficiency of CORR reaches 15.9% when the voltage is-0.83 V (vs.RHE).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of catalyst preparation, and particularly relates to a method for preparing a Cu-based catalyst for electrocatalytic reduction of low-concentration CO, in particular to a method for preparing a multi-grain boundary Cu-based catalyst with twinned copper species and application thereof. Background Art

[0002] In the context of the rapid development of modern industrialized society, the extensive use of fossil fuels has led to a large amount of CO 2 Emissions have destroyed the carbon balance in the ecological environment and caused environmental problems such as global warming. At the same time, incomplete combustion of fuels has also caused a large amount of CO to be discharged into the atmosphere, causing the atmospheric CO content in some areas to exceed the standard, posing a threat to the health of exposed people. Finding efficient and stable technologies to recover and utilize low-concentration CO in flue gas is of great significance for preventing and controlling CO pollution, maintaining carbon balance and promoting the recycling of carbon resources.

[0003] Electrocatalytic reduction of CO (CORR) using renewable electricity is an effective way to convert CO into high-value chemicals such as ethanol, acetic acid, and n-propanol. 2 , the conversion rate and Faraday efficiency of electrocatalytic reduction of CO are higher, the energy consumption is lower, and it is more conducive to industrial application.

[0004] Electrocatalysts play a crucial role in the efficiency and product distribution of CO electrocatalytic reduction. Cu-based catalysts can electrocatalytically reduce CO to multi-carbon products and are currently the most widely studied type of CORR catalysts, which mainly include single crystal Cu catalysts, bimetallic catalysts, oxide-derived Cu catalysts, and nitrogen-doped Cu catalysts. The electrocatalytic reduction of low-concentration CO is often accompanied by a strong competitive hydrogen evolution reaction (HER). How to improve the Faraday efficiency of low-concentration CO reduction is a key issue that must be addressed in the development and design of CORR catalysts.

[0005] The grain boundaries in the catalyst promote the adsorption and coupling of CO molecules, which not only improves the activity of electrocatalytic reduction of CO and the selectivity of products, but also increases the current density. In particular, the Cu-based catalyst with nano-twin structure not only has abundant grain boundaries, which can provide more active sites for the adsorption and conversion of CO, but also has good stability and good catalyst durability.

[0006] In order to increase the stability of catalyst materials during use and the convenience of material manufacturing, the in-situ growth method of electrodeposition is often used to load the catalyst on the gas diffusion layer, which can avoid the problems of increased catalyst layer impedance and poor long-term stability caused by the use of organic adhesives such as Nafion to adhere catalysts.

[0007] There are reports on the preparation of nano-twinned Cu catalysts by electrodeposition, but they are mainly used in the field of microelectronic device technology (CN 116631737 A). However, there are no reports on nano-twinned Cu catalysts for electrocatalytic reduction of low-concentration CO. Summary of the invention

[0008] The purpose of the present invention is to solve the problem of low Faraday efficiency in electrocatalytic reduction of low-concentration CO, and provide a multi-grain boundary Cu-based catalyst for electrocatalytic reduction of low-concentration CO and a preparation method thereof.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions:

[0010] The present invention provides a method for preparing a multi-grain boundary Cu-based catalyst for electrocatalytic reduction of low-concentration CO, the preparation method comprising the following steps:

[0011] (1) Add a certain amount of concentrated sulfuric acid to water, stir evenly at room temperature, then add a certain amount of anhydrous copper sulfate and sodium chloride, stir at room temperature until completely dissolved;

[0012] (2) adding a certain amount of gelatin to the solution prepared in step (1), heating and stirring in a water bath at 50 to 70° C. until the gelatin is completely dissolved;

[0013] (3) placing the solution obtained in step (2) in an electrolytic cell, and then placing the electrolytic cell in a water bath at 50-70° C., using the foamed copper as the anode and the gas diffusion layer as the cathode, and using a direct current electroplating method to load a certain amount of Cu on the gas diffusion layer. After the electroplating is completed, the gas diffusion layer is taken out, washed with water, and then dried under vacuum conditions to obtain the gas diffusion layer-loaded multi-grain boundary Cu-based catalyst.

[0014] In the preparation method of the present invention, in step (1), the volume ratio of concentrated sulfuric acid to water is 1-10:100; the mass ratio of anhydrous copper sulfate to water is 10-20%; and the mass ratio of sodium chloride to water is 200-300 ppm.

[0015] In the preparation method of the present invention, the mass ratio of gelatin to water in step (2) is 50 to 1000 ppm.

[0016] In the preparation method of the present invention, the gas diffusion layer in step (3) is preferably carbon fiber paper with a carbon powder layer.

[0017] In the preparation method of the present invention, in step (3), direct current electroplating is performed in a constant voltage manner. Preferably, the electroplating voltage is 2 to 5 V and the current density is 10 to 15 mA / cm 2 The electroplating time is 10 to 20 minutes; during electroplating, the solution is slowly stirred by magnetic or mechanical stirring.

[0018] In the preparation method of the present invention, the gas diffusion layer is washed with water at least three times after electroplating in step (3); the vacuum drying temperature is 50-80° C., and the drying time is 1-3 hours.

[0019] In the preparation method of the present invention, ultrapure water is preferably used for preparing the solution and washing.

[0020] The present invention provides a gas diffusion layer loaded multi-grain boundary Cu-based catalyst (with abundant twin crystal structure and grain boundaries) prepared by the preparation method.

[0021] The catalyst is a multi-grain boundary Cu particle with a twin structure tightly loaded on a gas diffusion layer; the average particle size of the Cu particle is less than 2 μm; the Cu loading on the gas diffusion layer is 1 to 4 mg / cm 2 .

[0022] The catalyst can be used for electrocatalytic reduction of N at room temperature and pressure 2 The low concentration of CO contained in the reaction mixture, the CO reduction products are mainly ethanol, acetic acid and methane; when the CO concentration is 5%, the total Faraday efficiency of the products is higher than 15%.

[0023] The technical solution provided by the present invention has at least the following technical effects:

[0024] (1) The present invention adopts an electrodeposition method to make Cu catalyst particles grow in situ on the gas diffusion layer. After the catalyst is prepared, a gas diffusion electrode that can be directly used is obtained. The preparation process is simple and the cost is low.

[0025] (2) The Cu-based catalyst prepared in the present invention has a twin structure and abundant grain boundaries, which can improve the efficiency of electron transfer in the electrocatalytic process and reduce the potential required for CO reduction;

[0026] (3) The multi-grain boundary Cu-based catalyst prepared in the present invention is conducive to the adsorption and coupling of CO molecules, thereby improving C 2+ Faradaic efficiency of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The scanning electron microscope characterization images of Example 1 and Comparative Example 1 of the present invention, wherein Figure a is a scanning electron microscope (SEM) image of Example 1, Figure b is a SEM image of Comparative Example 1, Figure c is an electron backscatter diffraction (EBSD) image of Example 1, and Figure d is an EBSD image of Comparative Example 1;

[0028] Figure 2 X-ray diffraction (XRD) diagrams of Example 1 and Comparative Example 1 of the present invention;

[0029] Figure 3The X-ray photoelectron spectroscopy (XPS) diagrams of Example 1 and Comparative Example 1 of the present invention are shown;

[0030] Figure 4 Graph showing the total Faraday efficiency of CORR of Example 1, Example 2 and Comparative Example 1 of the present invention;

[0031] Figure 5 This is a stability test diagram of Example 1 of the present invention;

[0032] Figure 6 is the gas phase product chromatogram of Example 1 of the present invention;

[0033] Figure 7 The liquid phase product nuclear magnetic resonance spectrum of Example 1 of the present invention ( 1 H-NMR) chart. DETAILED DESCRIPTION

[0034] A multi-grain boundary Cu-based catalyst for electrocatalytic reduction of low-concentration CO and a preparation method thereof are further described below in conjunction with the accompanying drawings and specific embodiments.

[0035] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0036] CORR Faraday efficiency test method: The prepared gas diffusion electrode was cut into a size of 2.0 cm × 2.0 cm and used as the working electrode, nickel foam was used as the counter electrode, and Hg / HgO electrode was used as the reference electrode. The electrocatalytic reduction of CO performance was tested in a flow-type electrolytic cell using a constant voltage method. The test voltage range was -0.6 to -0.9 V (vs. RHE). The electrolyte used in the cathode chamber and the anode chamber was 1 M KOH solution. During the reaction, 5% CO / N was introduced into the cathode chamber. 2 , the gas flow rate was 10mL / min. When testing the Faraday efficiency at different voltages, the reaction time at each voltage was 30min; when testing the stability of the catalyst, the voltage was fixed at -0.83V (vs. RHE). Gas chromatography was used to analyze and identify the gas phase products. 1 The liquid phase products were analyzed and identified by H-NMR, and dimethyl sulfoxide (DMSO) was used as the internal standard solution to calculate the selectivity and Faraday efficiency of each product.

[0037] Example 1

[0038] A multi-grain boundary Cu-based catalyst for electrocatalytic reduction of low-concentration CO and a preparation method thereof, wherein the preparation steps are as follows:

[0039] (1) Dissolve 10 mL of concentrated sulfuric acid in 200 mL of ultrapure water, stir evenly at room temperature, then add 30 g of anhydrous copper sulfate and 50 mg of sodium chloride respectively, and stir at room temperature until the anhydrous copper sulfate and sodium chloride are completely dissolved;

[0040] (2) adding 100 mg of gelatin to the solution prepared in step (1), heating and stirring in a 60° C. water bath for 3 hours to ensure that the gelatin is completely dissolved;

[0041] (3) placing the solution obtained in step (2) in a Hastelloy electrolytic cell with a cathode-cathode distance of 5 cm, placing the electrolytic cell in a 60° C. water bath, and stirring the solution by magnetic stirring at a speed of 100 rpm;

[0042] (4) placing a carbon fiber paper with a carbon powder layer at the cathode of an electrolytic cell, with the area of ​​the carbon fiber paper immersed in the electrolyte being 2.5 cm × 2.5 cm, and placing a 3 mm thick copper foam at the anode of the electrolytic cell;

[0043] (5) A DC voltage of 3 V was applied between the cathode and anode of the electrolytic cell. After electroplating for 20 min, the carbon fiber paper was taken out, washed three times with ultrapure water, and dried in a vacuum oven at a temperature of 60° C. for 2 h. After drying, the paper was cut into pieces of 2.0 cm×2.0 cm to obtain a gas diffusion electrode containing a multi-grain boundary Cu-based catalyst.

[0044] The SEM and EBSD characterization results of the obtained catalysts are shown in Figure 1 As shown in a and c. Figure 1 Middle a shows that the apparent particle size of the in-situ grown catalyst particles is less than 2 μm; Figure 1 Middle c shows that the catalyst has rich twin structure and grain boundaries.

[0045] The XRD and XPS spectra of the obtained catalyst are shown in Figure 2 and 3 shown. Figure 2 It is shown that the main crystalline phase of the catalyst is Cu (PDF#85-1326), while Figure 3 This indicates that the Cu in the catalyst is mainly elemental Cu, with a small amount of Cu 2+ , which may come from the oxidation of surface Cu during the drying process.

[0046] The above characterization results show that the obtained catalyst is Cu particles with rich twin structure and grain boundaries, and the average particle size is less than 2μm.

[0047] The Faradaic efficiency of the obtained catalyst for electrocatalytic reduction of low concentration CO was tested. Figure 4 As shown, it can be seen that the highest total Faradaic efficiency of 15.9% is obtained when a voltage of -0.83 V (vs. RHE) is applied.

[0048] The stability of the catalyst was tested. Figure 5 It can be seen that when the current density is maintained at 21 mA / cm2 at a voltage of -0.83 V (vs. RHE) for 13 h. 2 , the total Faradaic efficiency remained at around 15.5%, indicating that the catalyst had good stability.

[0049] Using gas chromatography and 1 The gas phase and liquid phase products were tested by H-NMR method. Figure 6 and 7 shown. Figure 6 This indicates that the gas phase products, in addition to H 2 , and trace amounts of methane; Figure 7 The results showed that the liquid products were mainly acetic acid and ethanol, accompanied by a small amount of n-propanol and methanol.

[0050] Example 2

[0051] The preparation method of the catalyst is as described in Example 1, but the amount of gelatin added in step (2) is 20 mg.

[0052] The Faradaic efficiency of the obtained catalyst for electrocatalytic reduction of low concentration CO was tested. Figure 4 As shown, it can be seen that the highest total Faradaic efficiency of 12.1% is obtained when a voltage of -0.79 V (vs. RHE) is applied.

[0053] from Figure 4 It can also be seen that within the tested voltage range, the CORR total Faraday efficiency of the catalyst obtained in Example 1 is significantly higher than that in Example 2, which indicates that adding a suitable amount of gelatin during the catalyst preparation process is beneficial to improving the performance of the catalyst.

[0054] Comparative Example 1

[0055] The preparation method of the catalyst is as described in Example 1, but gelatin is not added in step (2).

[0056] The SEM and EBSD characterization results of the obtained catalysts are shown in Figure 1 As shown in b and 1d. Figure 1 Middle b shows that the apparent particle size of the in-situ grown catalyst particles is > 2 μm; Figure 1 Middle (d) shows that the catalyst has only a small amount of twin structure and grain boundaries.

[0057] The XRD and XPS spectra of the obtained catalyst are shown in Figure 2 and 3 As shown. It can be seen that the main crystal phase of the catalyst is also Cu( Figure 2 ); In addition to Cu, it also contains a small amount of Cu 2+ ( Figure 3 ).

[0058] The above characterization results show that the crystal phase and valence composition of the obtained catalyst are not significantly different from those of Example 1, but the catalyst particles are larger and have fewer twin structures and grain boundaries.

[0059] The Faradaic efficiency of the obtained catalyst for electrocatalytic reduction of low concentration CO was tested. Figure 4 As shown, it can be seen that the highest total Faradaic efficiency of 10.9% is obtained when a voltage of -0.79 V (vs. RHE) is applied.

[0060] from Figure 4 It can also be seen that within the tested voltage range, the CORR total Faraday efficiency of the catalysts obtained in Examples 1 and 2 is significantly higher than that of Comparative Example 1, which fully demonstrates the superiority of the preparation method of the present invention.

[0061] Finally, it should be emphasized that the above embodiments are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications, and any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a multi-grain boundary Cu-based catalyst for electrocatalytic reduction of low-concentration CO, characterized in that: The preparation method comprises the following steps: (1) Add a certain amount of concentrated sulfuric acid to water, stir evenly at room temperature, then add a certain amount of anhydrous copper sulfate and sodium chloride, stir at room temperature until completely dissolved; (2) adding a certain amount of gelatin to the solution prepared in step (1), heating and stirring in a water bath at 50 to 70° C. until the gelatin is completely dissolved; (3) placing the solution obtained in step (2) in an electrolytic cell, and then placing the electrolytic cell in a water bath at 50-70° C., using the foamed copper as the anode and the gas diffusion layer as the cathode, and using a direct current electroplating method to load a certain amount of Cu on the gas diffusion layer. After the electroplating is completed, the gas diffusion layer is taken out, washed with water, and then dried under vacuum conditions to obtain the gas diffusion layer-loaded multi-grain boundary Cu-based catalyst.

2. The method according to claim 1, characterized in that In step (1), the volume ratio of concentrated sulfuric acid to water is 1-10:100; the mass ratio of anhydrous copper sulfate to water is 10-20%; and the mass ratio of sodium chloride to water is 200-300 ppm.

3. The method according to claim 1, characterized in that In step (2), the mass ratio of gelatin to water is 50 to 1000 ppm.

4. The method according to claim 1, characterized in that The gas diffusion layer in step (3) is preferably carbon fiber paper with a carbon powder layer.

5. The method according to claim 1, characterized in that In step (3), direct current electroplating is performed in a constant voltage manner. Preferably, the electroplating voltage is 2 to 5 V and the current density is 10 to 15 mA / cm 2 The electroplating time is 10 to 20 minutes; during electroplating, the solution is slowly stirred by magnetic or mechanical stirring.

6. The method according to claim 1, characterized in that In step (3), the gas diffusion layer is washed with water at least three times after electroplating; the vacuum drying temperature is 50 to 80° C., and the drying time is 1 to 3 hours.

7. The method according to claim 1, characterized in that Ultrapure water is preferred for preparing solutions and washing.

8. The method according to claim 1, characterized in that The catalyst is a multi-grain boundary Cu particle with a twin structure tightly loaded on a gas diffusion layer; the average particle size of the Cu particle is less than 2 μm; the Cu loading on the gas diffusion layer is 1 to 4 mg / cm 2 .

9. A multi-grain boundary Cu-based catalyst obtained according to the method of any one of claims 1 to 8.

10. Use of the multi-grain boundary Cu-based catalyst obtained by the method according to any one of claims 1 to 8 for electrocatalytic reduction of low-concentration CO contained in N2 at room temperature and pressure, wherein the CO reduction products are mainly ethanol, acetic acid and methane; when the CO concentration is 5%, the total Faraday efficiency of the product is higher than 15%.

Citation Information

Patent Citations

  • Nano twin-crystal copper micro-inductor and preparation method and application thereof

    CN116631737A

Cited By

  • Series catalyst, preparation method and application of series catalyst in electroreduction of carbon dioxide

    CN121826783A